2018
DOI: 10.3390/sym10030069
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Symmetric Collaboration in Public Spaces through 3D Mobile Interaction

Abstract: Collaboration has been common in workplaces in various engineering settings and in our daily activities. However, how to effectively engage collaborators with collaborative tasks has long been an issue due to various situational and technical constraints. The research in this paper addresses the issue in a specific scenario, which is how to enable users to interact with public information from their own perspective. We describe a 3D mobile interaction technique that allows users to collaborate with other peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Kim et al proposed adaptive mobile resource offloading (AMRO), which is a load-balancing scheme for processing large-scale jobs using mobile resources without a cloud server, which is applied in a mobile cloud computing environment based on collaborative architecture [25]. Machuca et al describe a 3D mobile interaction technique that allows users to collaborate with other people by creating a symmetric and collaborative ambience [26]. Wu et al proposed a novel method for collaborative computer aided design (Co-CAD) synchronization, in which all Co-CAD sites maintain symmetric and consistent operating procedures [27].…”
Section: Symmetric Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al proposed adaptive mobile resource offloading (AMRO), which is a load-balancing scheme for processing large-scale jobs using mobile resources without a cloud server, which is applied in a mobile cloud computing environment based on collaborative architecture [25]. Machuca et al describe a 3D mobile interaction technique that allows users to collaborate with other people by creating a symmetric and collaborative ambience [26]. Wu et al proposed a novel method for collaborative computer aided design (Co-CAD) synchronization, in which all Co-CAD sites maintain symmetric and consistent operating procedures [27].…”
Section: Symmetric Decision-makingmentioning
confidence: 99%
“…Considering the distribution and symmetry of the planning and decision-making processes in the shipbuilding projects, an appropriate decision-making method and tool to assist the participants to make better decisions is extremely important. There are many researches on symmetric decision-making theory, including the decision-making model [19][20][21][22][23] and decision-making system modeling [24][25][26][27][28][29]. The purpose of this paper is to provide effective decision-making methods for project participants.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional real-world multi-display environments, such as command-and-control rooms, combine various displays (wall displays, desktops, and digital tabletops) that research has shown each serves a particular purpose: wall displays and tabletops are commonly used for group awareness and collaboration, and tablets or desktops for personal work [20,56,64,80]. Research on the topic has gone further, combining wall displays, in particular,with portable devices, such as smartwatches, mobile phones, or tablets, that can act as private displays or input devices when users are further away from the wall, and direct touch is not possible [19,31,52,77].…”
Section: Introductionmentioning
confidence: 99%